2018
DOI: 10.1016/j.mex.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Retinal tissue preparation for high-resolution live imaging of photoreceptors expressing multiple transgenes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The most common detection methods for miRNAs are qRT-PCR and microarray; they are strongly dependent on the precision of the extraction methods [75]. Therefore, it is imperative to optimize and standardize the miRNA isolation methods/ procedure [76]. Many studies reported discrepancies in miRNA measurement and recovery because of the extraction methods [68,77].…”
Section: Selection Of Sample Source and Mirnas Extraction Methodsmentioning
confidence: 99%
“…The most common detection methods for miRNAs are qRT-PCR and microarray; they are strongly dependent on the precision of the extraction methods [75]. Therefore, it is imperative to optimize and standardize the miRNA isolation methods/ procedure [76]. Many studies reported discrepancies in miRNA measurement and recovery because of the extraction methods [68,77].…”
Section: Selection Of Sample Source and Mirnas Extraction Methodsmentioning
confidence: 99%